Barbados' 2018-19 Sovereign Debt Restructuring-A Sea Change? - Anthony, Myrvin (IMF Working Papers; Working Paper, 2020)
This paper examines the causes, processes, and outcomes of Barbados' 2018-19 sovereign debt restructuring-its first ever. The restructuring was comprehensive, featuring several rarely used approaches, including the restructuring of treasury bills, and the use of a retrofitted collective action mechanism. The debt restructuring has helped to set Barbados' public debt on a clear downward trajectory. A sustained reform effort, maintaining high primary surpluses and ambitious structural reforms, will be needed to gradually reduce public debt from about 160 percent of GDP before the restructuring to the country's 60 percent debt-to-GDP target.